2019
DOI: 10.1038/s41387-019-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous advanced glycation end products in pancreatic islets after short-term carbohydrate intervention in obese, diabetes-prone mice

Abstract: Diet-induced hyperglycemia is described as one major contributor to the formation of advanced glycation end products (AGEs) under inflammatory conditions, crucial in type 2 diabetes progression. Previous studies have indicated high postprandial plasma AGE-levels in diabetic patients and after long-term carbohydrate feeding in animal models. Pancreatic islets play a key role in glucose metabolism; thus, their susceptibility to glycation reactions due to high amounts of dietary carbohydrates is of special intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
0
35
0
2
Order By: Relevance
“…AGEs are compounds that are formed from proteins and peptides by non-enzymatic glycoxidation reactions after interaction with aldose sugars (Chih-Tsueng et al, 2014; Richard et al, 2019). In this process, there is the nucleophilic addition of the free amino groups from proteins, lipids or nucleic acids to the carbonyl groups of monosaccharides.…”
Section: Ages-overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…AGEs are compounds that are formed from proteins and peptides by non-enzymatic glycoxidation reactions after interaction with aldose sugars (Chih-Tsueng et al, 2014; Richard et al, 2019). In this process, there is the nucleophilic addition of the free amino groups from proteins, lipids or nucleic acids to the carbonyl groups of monosaccharides.…”
Section: Ages-overviewmentioning
confidence: 99%
“…In this process, there is the nucleophilic addition of the free amino groups from proteins, lipids or nucleic acids to the carbonyl groups of monosaccharides. This reaction (known as Maillard reaction) forms a reversible Schiff base adduct that spontaneously undergoes Amadori rearrangement to form the reactive dicarbonyls or ketamines when the attachment becomes irreversible (Vasudevan et al, 2013; Scheijen et al, 2018; Richard et al, 2019) as shown in Figure 1.…”
Section: Ages-overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Subgroups were fed with a carbohydrate-rich diet [+CH, 20% (wt/wt) protein, 28% (wt/wt) fat and 40% (wt/wt) carbohydrates] for a maximum of 21 days (for detailed diet compositions, see Ref. [ 23 ]). A further extension of the metabolic challenge was not permitted for animal welfare reasons.…”
Section: Methodsmentioning
confidence: 99%